Law and religion in the liberal state - Bhuiyan, Jahid Hossain; Jensen, Darryn (London [England] : Hart Publishing, 2020)
"The relationship between law and religion is evident throughout history. They have never been completely independent from each other. There is no doubt that religion has played an important role in providing the underlying values of modern laws, in setting the terms of the relationship between the individual and the state, and in demanding a space for the variety of intermediate institutions which stand between individuals and the state. However, the relationships between law and religion, and the state and religious institutions differ significantly from one modern state to another. There is not one liberalism but many. This work brings together reflections upon the relationship between religion and the law from the perspectives of different sub-traditions within the broader liberal project and in light of some contemporary problems in the accommodation of religious and secular authority."--
9. Religious Exemptions from Civil Laws and Free Exercise of Religion in the USA -- I. Introduction -- II. Are Religious Exemptions a Constitutional Right? -- III. The Outlook for Religious Exemptions -- 10. Whose Conscience? Which Complicity? Reconciling Burdens and Interests in the Law of Religious Liberty -- I. Introduction -- II. How RFRA Helps Religious Believers, Sometimes -- III. How RFRA Hurts Others, Sometimes: The Case of Hobby Lobby -- IV. A Study in Contrasts: Two Recent Cases -- V. Conclusion: What Next? -- 11. Sanctuary: Religion and Law in the United States -- I. Introduction
Description based upon print version of record.
II. The Religious Roots of Sanctuary
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Religion and state; Freedom of religion; Religious minorities -- Legal status, laws, etc; Law; Electronic books